B2B Brand Management and Private Labels Products - Flavio Gnecchi (European Scientific Journal, ESJ, 2018)
Brand management always requires the definition of a strategy, in order to maintain and strengthen relationships with customers. Brand management makes it possible for companies to pursue a variety of goals, which is the aim of every company. This is irrespective of the fact that every organization can scale their intensity and priorities on the basis of their specific strategic guidelines, influenced by endogenous and exogenous variables to the company. Also in B2B, it is crucial to properly assess the opportunities, and the related commitments, linked to brand management. A particular businessto- business context occurs due to the progressively growing phenomenon of private labels. After their success in supermarkets, private labels have also gained a foothold in the wholesale trade. Therefore, for some manufacturing firms, a different channel is feasible and is represented by commercial companies that wish to submit their own brand products to end customers (supermarket chains) and professional operators (wholesale warehouses).